PEMAHAMAN MATEMATIS DITINJAU DARI GAYA BELAJAR SISWA - Nasrul Khotimah; M. Zainudin (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2023)
The purpose of this study was to analyze the ability of mathematical understanding in terms of student learning styles. The method used is literature study, by collecting library data, journals, articles, reading, taking notes, and processing research results. This study shows that differences in learning styles affect students' mathematical understanding. Based on the three learning styles, namely visual, auditory, and kinesthetic learning styles, there are differences in understanding of mathematical concepts. The dominant learning styles used by students are visual learning styles and auditory learning styles. Based on the results of the study, it can be concluded that the auditory learning style has a higher ability than other learning styles.